Pengaruh keluarga dan lingkungan dalam pengembangkan jiwa sosial dalam diri anak hingga remaja - Sobih, Muhammad (Maliki Interdisciplinary Journal, 2024)
Social psyche is an important aspect of child and adolescent development that affects how they interact with the environment, build relationships and contribute to society. The family, as the first environment that children are exposed to, plays a vital role in shaping children's social attitudes and behaviors. Values such as empathy, cooperation and responsibility are first taught at home. Supportive and loving parenting patterns provide a sense of security for children to learn to socialize, while authoritarian parenting can hinder social development. Beyond the family, environments such as school and peers also play an important role in expanding a child's social experiences. Extracurricular activities and social groups help adolescents form a more complex social identity. The relationship between the family and the external environment is mutually influential, with strong family support making it easier for children to face social challenges outside the home. In adolescence, the influence of peer groups becomes more dominant, but a strong social foundation from the family remains an important foundation in dealing with social pressures and making wise decisions.